EVALUASI PROGRAM PELAKSANAAN SEATEACHER DI THAILAND DAN FILIPINA MENGGUNAKAN MODEL CIPP - Dahlia, Siti; ASTUTI, SRI; FITRIANA, ONNY (Idaarah: Jurnal Manajemen Pendidikan, 2019)
The aim of research is evaluation SeaTeacher Programme based on Context, Input, Process, and Product analysis. This research conducted based on qualitatif evaluation method using Context, Input, Process, and Product model. The data collection used observation, dokumentation, and interview method. The result of research shows that based on contexts analysis the programme is good, because there are legal basis programme such as MoU, conformity with strategic plans, and curiculum needs. Based on input analysis that the programme is not optimal, because there are no training and workshop for students related curiculum and culture of destination country. Evaluation programme based on process is good, because there are conformity related schedule, supervisor, and teaching and learning process. Based on product evaluation is good also, because students who joined the program get soft skills, link, and excellent score. Moreover, the students have self report about the programme that they should upload on SeaMeo website. In summary, according to evalutaion the programme is good, while it need improvement for many aspects.